Education On Handling Choking On Babies And Children In Dusun 1 Kismoyoso Village - Chintya Hayu (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
Choking is a very dangerous emergency, because in a few minutes there will be a general or complete lack of oxygen so that in just minutes the client will lose reflexes, heart rate and death permanently from the brain stem. The method carried out is socialization regarding the handling of choking on infants and children in Hamlet 1, Kismoyoso Village, Ngemplak District, Boyolali Regency, Central Java which was carried out on Saturday, August 5, 2023. This socialization is in the form of material presentation and gives examples of what techniques can be used if the baby/child chokes. The purpose of socializing the handling of choking babies is to prevent the occurrence of significant negative impacts on infants and children caused by choking. With this socialization, it is hoped that parents can provide first aid with several techniques. Keywords: signs, factors, prevention and treatment of choking in infants